1 - sin^2(x) - 2 * sin(x) +1 = 0
sin^2(x) + 2 * sin(x) - 2 = 0
sin(x) = (-2 +-√(4 - 4 * (-2)) /2 = (-2 +-2)/2
sin(x) = 0 sin(x) = -2 - корней не имеет.
x = 0 + 2πn, где n натуральное число.
наверно так я не знаю возможно ошибся если чё сори.Первый раз делал.
1 - sin^2(x) - 2 * sin(x) +1 = 0
sin^2(x) + 2 * sin(x) - 2 = 0
sin(x) = (-2 +-√(4 - 4 * (-2)) /2 = (-2 +-2)/2
sin(x) = 0 sin(x) = -2 - корней не имеет.
x = 0 + 2πn, где n натуральное число.
наверно так я не знаю возможно ошибся если чё сори.Первый раз делал.